Enhancing the performance of robotic arm system using fuzzy logic and PID controller - Abbas Hussein Al-khazarji, Hasan (International Journal of Engineering and Technology, 2019)
The aim of this paper is to obtain the best performance of robotic arm response by using fuzzy logic controller compared with conventional PID controller. The robotic arm is simulated using dynamic model of motion equations inside Matlab environment. The high percent of overshoot found in conventional PID controller which exceeds 40% is addressed by optimizing parameters Kp, Ki and Kd by using the proposed fuzzy logic controller. The simulation results view zero percent of overshoot and fast response (settling time and rise time) found by the obtained result is implementation.Â Â